Scleroderma and its oral implications. (2nd November 2022) - Saeed, Khadeeja; Kumar, Navdeep
Abstract : Scleroderma is an autoimmune condition of the connective tissue. It encompasses a range of disorders that can affect the face, skin, limbs and internal organs. Common dental manifestations include xerostomia, dysphagia, microstomia, thickened and tight facial skin and tongue rigidity. This article describes how scleroderma can severely impact and compromise oral health. This can occur due to the restricting nature of sclerodactyly and microstomia seen in severe forms of the disease. Dental professionals must be mindful of this condition and its common oral manifestations. Techniques of how to recognize and manage these patients are discussed. CPD/Clinical Relevance: The dental and oral health implications of scleroderma are relevant to clinical practice.